More Accurate Diagnosis of Vitreoretinal Lymphoma Using a Combination of Diagnostic Test Results: A Prospective Observational Study. (18th August 2022) - Tanaka, Rie; Kaburaki, Toshikatsu; Taoka, Kazuki; Karakawa, Ayako; Tsuji, Hideki; Nishikawa, Masako; Yatomi, Yutaka; Shinozaki‐Ushiku, Aya; Ushiku, Tetsuo; Araki, Fumiyuki
ABSTRACT: Purpose: To establish diagnostic criteria for vitreoretinal lymphoma (VRL) using cytology and laboratory tests from vitreous samples: interleukin (IL)-10/IL-6 ratio, immunoglobulin (Ig) H gene rearrangement, and clonal B-cells on flow cytometry. Methods: Fifty-six patients with and 39 without VRL were included. We assessed the sensitivity and specificity of each test and those of diagnostic criteria based on combinations of these tests. Results: The sensitivity values for malignant cytology, IL-10/IL-6 > 1, IgH gene rearrangement, and flow cytometry were 0.554, 0.821, 0.732, and 0.625 with specificity of 1.000, 1.000, 0.846, and 0.974, respectively. When the diagnostic criteria were set at malignant cytology or at two or more of of four tests (atypical cells, IL-10/IL-6 > 1, IgH gene rearrangement, and flow cytometry), the sensitivity and specificity values for accurate diagnosis were 0.929 and 1.00, respectively. Conclusion: Malignant cytology or positive results for two or more of four tests may be adequate for VRL diagnosis.